Treatment of extranodal NK/T-cell lymphoma: From past to future - Yan, Zheng; Yao, Shuna; Wang, Zhizhong; Zhou, Wenping; Yao, Zhihua; Liu, Yanyan (Frontiers in Immunology, 2023)
Extranodal NK/T-cell lymphoma (ENKTCL) is the most common subtype of T/NK-cell lymphoma in Asia and Latin America but very rare in North American and Europe. Patient survival has improved significantly over the past two decades. However, standard treatment has not yet been established, although dozens of prospective trials have been conducted. To help understand how the treatment of this aggressive malignancy has evolved in the past and what trends lie ahead, we comprehensively review the treatment of ENKTCL, with a particular focus on neglected issues. Overall, the 5-year overall survival (OS) of patients with Ann Arbor stage I/II disease increased from < 50% in the early 20th century to > 80% in recent years, and the median OS of patients with Ann Arbor stage III/IV disease increased from < one year to more than 3 years. The improved patient survival is largely attributable to advances in radiation technology, and the introduction of asparaginase (Asp) and anti-PD-1/PD-L1 immunotherapy into practice. Radiotherapy is essential for patients with early-stage disease, and Asp-based chemotherapy (CT) and PD-1/PD-L1 inhibitors can significantly improve outcomes of patients with advanced-stage disease. ENKTCL management is displaying a trend toward more simplified regimens, less toxicity, and higher efficacy. Novel drugs, such as manufactured T cells, monoclonal antibodies, and small molecule inhibitors, are under intensive investigation. In the future, it is unnecessary to consume more resources to compare different combinations of Asp with cytotoxic agents. Instead, more efforts should be made to optimize the use of Asp and immunotherapy to maximize efficacy and minimize toxicity, explore approaches to overcoming resistance to Asp and immunotherapy, identify novel treatment targets, and define subpopulations who can benefit more from specific treatments.